Analysis of Financial Ratios to Evaluate the Financial Performance of PT GarudaFood Putra Putri Jaya Tbk in 2020-2022 - Sabda Dian Nurani Siahaan; Ananda Putri Utami; Fahrul Alhamdi Hafiz; Fildzah Haryani Harahap; Intan Nur’aini (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to identify the description of the financial performance of PT. Garudafood for the 2020-2022 period. The identified relationships will help managers and decision-makers to predict the company's future performance through the organization's financial ratios. In this research analysis, liquidity, solvency, activity, profitability, and financial ratios are used to assess the financial performance of PT. Garudafood. This research was conducted using a qualitative research method carried out with a descriptive approach. Based on the research results, it is known that the form of financial ratios is complex, and the complexity is influenced by the complexity of financial reports. It should be noted that the complexity of financial reports is increasing, not only because the financial and accounting principles used are increasingly complex and numerous, but also because the numbers presented are fixed numbers. Not much innovation in the presentation of financial statements.